Online Single Submission (OSS) Based on E-Government Implementation in Micro Small Medium Business Licensing (MSMEs) - Astri Siti Fatimah (Journal of Governance, 2022)
The era of discourse marked by the use of technology in various fields of life has changed people's habitual patterns from manual to digital. Of course, this has positive and negative impacts on human life. Positive because everything can be done very easily, cheaply, and quickly, and because it can be accessed from anywhere. The downside is dependence on electricity supply and cellular networks. Based on the results of the research, it was found that the Central Government, as the development agent, has attempted to launch OSS with various types of public services under one roof. Here, the synergy and commitment of the regional government are needed to create a competitive, innovative, and creative environment, as well as the need for massive socialization so that all stakeholders understand and can use this OSS properly. With this OSS-based e-government, the existence of MSMEs as the main pillar of the economy at the local, national, and international levels will be more resilient and strong with full transparency, efficiency, effectiveness, and accountability.